2021
DOI: 10.3390/cancers13092035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SSTR2 Expression in SI-NETs and Relation to Overall Survival after PRRT

Abstract: (1) Purpose: Small intestinal neuroendocrine tumors (SI-NETs) often present with distant metastases at diagnosis. Peptide receptor radionuclide therapy (PRRT) with radiolabeled somatostatin analogues is a systemic treatment that increases overall survival (OS) in SI-NET patients with stage IV disease. However, the treatment response after PRRT, which targets somatostatin receptor 2 (SSTR2), is variable and predictive factors have not been established. This exploratory study aims to evaluate if SSTR2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…SSTR2, as a G protein-coupled cell surface receptor, can be activated by extracellular ligands, which leads to the inhibition of cell proliferation ( Lechner et al, 2021 ). Precious studies demonstrated that SSTR2 might serve as a molecular target in the diagnosis and treatment of thyroid cancer ( Thakur et al, 2021 ), small intestinal neuroendocrine tumor ( Elf et al, 2021 ), and neuroendocrine tumors ( Si et al, 2021 ). VIP can provide protection from apoptosis in tumorigenesis ( Sastry et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…SSTR2, as a G protein-coupled cell surface receptor, can be activated by extracellular ligands, which leads to the inhibition of cell proliferation ( Lechner et al, 2021 ). Precious studies demonstrated that SSTR2 might serve as a molecular target in the diagnosis and treatment of thyroid cancer ( Thakur et al, 2021 ), small intestinal neuroendocrine tumor ( Elf et al, 2021 ), and neuroendocrine tumors ( Si et al, 2021 ). VIP can provide protection from apoptosis in tumorigenesis ( Sastry et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity is also pronounced in their endocrine activities and tumor growth, possibly because GI-NETs originate from a variety of neuroendocrine cells located in different sites [10]. Almost all GI-NETs have been reported to express somatostatin receptors (SSTRs), and their expression profiles have also been known to be heterogeneous [7,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Various scoring systems of SSTR2 immunoreactivity based on eyeball analysis, such as Volante score [18,19] and Immunoreactivity Score [11,20], have been proposed in order to yield a more reproducible and subjective interpretation of results toward establishing a better correlation between SSTR2 immunohistochemistry results and SSAs' therapeutic efficacy. However, these attempts have been mostly reported in PanNETs, not in GI-NETs.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine tumors are tumors of neuroendocrine cells, usually associated with high expression of somatostatin receptor subtype 2 (SSTR2) [1]. 68 Ga-DOTA-D Phe 1 ,Tyr 3 -octreotate ( 68 Ga-DOTATATE), a somatostatin analogue with high a nity for SSTR2, has been used in the imaging of neuroendocrine tumors [2]. Once SSTR2 expression is con rmed by 68 Ga-DOTATATE based imaging, the same SSTR2 analog, DOTATATE, can be attached to the therapeutic radioisotope ( 177 Lu, typically) and be used for molecular targeted therapy, which is called peptide receptor radionuclide therapy (PRRT) [3].…”
Section: Introductionmentioning
confidence: 99%
“…68 Ga-DOTA-D Phe 1 ,Tyr 3 -octreotate ( 68 Ga-DOTATATE), a somatostatin analogue with high a nity for SSTR2, has been used in the imaging of neuroendocrine tumors [2]. Once SSTR2 expression is con rmed by 68 Ga-DOTATATE based imaging, the same SSTR2 analog, DOTATATE, can be attached to the therapeutic radioisotope ( 177 Lu, typically) and be used for molecular targeted therapy, which is called peptide receptor radionuclide therapy (PRRT) [3]. The uptake of DOTATATE can be observed not only in tumor tissues, but also in normal organs, such as liver and spleen.…”
Section: Introductionmentioning
confidence: 99%